DRIVING THE FUTURE: UNDESTANDING THE INTENTION TO PURCHASE ELECTRIC VEHICLES OF YOUNG PEOPLE - Astuti, Septin Puji (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
Car sales increase along with the increasing number of populations. Unfortunately, modern transportation has negative consequences to environment. This situation led world leader to encourage vehicle manufacturers to develop more environmentally vehicle such as electric car that produce less pollution. Jakarta is one on leading market of car in Indonesia can be the main target of the electric car. However, the electric car in Indonesia is categorized an early developed vehicle and the market is very limited. This study examines the intention of young people in Jakarta, Bogor, Depok, Tangerang, and Bekasi to purchase electric car. Technology Acceptance Model (TAM) is applied in this study. The result shows that all variable of TAM has significant contribution to purchase intention. The influence of perceived ease of use to perceived usefulness is significant. This in turns affect to attitude towards using electric vehicle that contributes to the intention to purchase electric vehicle.